Hubungan Konsep Diri dan Kecerdasan Sosial dengan Hasil Belajar Ilmu Pengetahuan Sosial - Nurlinda Safitri (Pedagogia: Jurnal Ilmiah Pendidikan, 2016)
The aim of the research is to find out the correlation between self-concept and social quotient and students’ achievement on social science subject. The research is a correlational reseach conducted to the students of Bina Insani elementary school located at the district of Tanah Sareal, Bogor, with the number of population reached 125 students of all fifth grade classes. The number of the sample was gained by using Taro Yamane formula. From the total number of 125 students, those chosen as participants were only 95 students. The research used survey method with correlational technique. Based on the result of data analysis, the research shows that there is positive correlations among: 1) self-concept and the achievement on social science subject; 2) Social quotient and the achievement on social science subject; 3) both self-concept and social quotient and the achievement on social science subject. Based on the findings of the research, it can be inferred that the achievement of social science subject of the fifth grade students at SD Bina Insani located at the district of Tanah Sareal, Bogor can be improved by enhancing students’ self-concept and their social quotient.